ASPECTS OF TEACHING FOREIGN LANGUAGES AT A TECHNICAL UNIVERSITY - Z.T, Imamova. (International Journal of Psychosocial Rehabilitation, 2020)
In this article we will try to consider some methodological principles and features of teaching a foreign language in a technical university, based on the criteria for the development of professional competence. The emergence of the concept of competency-based approach - the "competence-based approach" in European higher education entailed a reassessment of the teaching methodology, including teaching a foreign language. The main goals and objectives of the new methodological approach in education were determined by the Commission “Pan-European Format of Foreign Language Proficiency: Training, Teaching, Level Assessment” At the pedagogical level, this approach means changing the paradigm of the teaching process, since the main emphasis is not on the transfer of knowledge by the teacher to the student, but on the activation of the role and motivation for students to search for information and teaching keys. At the methodological level, the specific goals of training programs within the framework of the “competence- based approach” are determined depending on the acquired competencies of future graduates. Such a statement of the problem absolutely corresponds to the structure of multidisciplinary education, or, since there is a practice of English designation, to the Liberal Arts system